Intervalo Parto-Concepción en Ganado Lechero Especializado de Costa Rica - La Roche Loaiza, Amed (2019)
An efficient dairy herd must produce a living, healthy calf per cow per year, and it should be accomplished with a Calving-Conception Interval (CCI) no greater than 100 days. Objective: Describe CCI epidemiological aspects in specialized dairy cattle in Costa Rica during the 2000-2013 period. Materials and methods: A historical prospective study was conducted with 434,708 entries from the VAMPP Bovino 3.0 software. CCI was estimated for intrinsic and extrinsic variables in cattle. Data was analyzed using descriptive statistics (mean, median, standard deviation, 95% confidence interval). Furthermore, means and percentages were compared using T-Student and Chi-square tests, respectively, while the risk of a CCI higher than 100 days was calculated by the rate radio (RR), using Poisson regression. Results: Over 50% of cattle had a CCI greater than 100 days, with a general mean of 136.6 days (± 84.2). CCI was higher in first lactation animals (142.0 ± 88.4 days) (P<0.001). It was also higher in Holstein cattle (148.7±85.9 days) than in Brown Swiss and Jersey cattle (P < 0.0001). Average CCI was higher in cattle with dystocic or cesarean deliveries (P < 0.001). Cattle with high milk production (5900-10100 kg/305d) exhibited a greater CCI (141.5 d ± 80.8 d). CCI of animals living in the dry forest was almost 10 days higher than those living in other areas (P<0.01). Those same weather conditions were the ones that showed the highest risk (rate ratio) with a CCI greater than 100 days. Conclusion. CCI is influenced by intrinsic and extrinsic variables. Therefore, herd management should focus on modifiable variables, such as heat detection and efficient artificial insemination.